INDIKASI RELATIF PADA PERSALINAN DENGAN SECTIO CAESAREA - Nur Lathifah; Topan Aditya Rahman; Yulia Safitri (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2019)
ABSTRACTBackground: Sectio Caesarea is performed with absolute or relative indications. On the relative indication, vaginal delivery can be accomplished but delivery with cesarean section will be safer for the mother, baby or both. In the last three years, the number of cesarean delivery in Dr. H. Moch. Ansari Saleh Banjarmasin has increased.Purpose: To analyze the relative indications associated with caesarean section delivery.Method: The method of this research use analytical survey with case control approach. The Population of this research are all parturient at Dr. H. Moch. Ansari Saleh Hospital Banjarmasin as many as 4776 parturient on 2015. Total number of sample cases are 515 sample with total sampling technique and sample control 515 sample with systematic random sampling technique. Data was collected by documentation maternal registration book technique. Data was analyzed with Chi Square test use (α=0,05).Result: Based on the results, the history of caesarean section (p=0,000;OR=19,529), breech delivery (p=0,000;OR=2,717), macrosomia (p=0,000;OR=24,028) are associated with caesarean section delivery. However, severe preeclampsia (p=0,0260) is not associated with caesarean section delivery.Conclusion: There is a significant association between the history of caesarean section, breech delivery and macrosomia with caesarean section delivery. While severe preeclampsia is not association with caesarean section delivery.Keywords: The Relative Indications, Caesarean Section INTISARILatar Belakang: Persalinan dengan Sectio Caesarea dilakukan dengan indikasi absolut atau relatif. Pada indikasi relatif, kelahiran lewat vagina bisa terlaksana tetapi pada keadaan tertentu kelahiran lewat sectio caesarea akan lebih aman bagi ibu, anak ataupun keduanya. Pada tiga tahun terakhir angka persalinan sectio caesarea di RSUD Dr. H. Moch. Ansari Saleh Banjarmasin mengalami peningkatan.Tujuan: Menganalisis Indikasi Relatif Yang Berhubungan Dengan Persalinan Sectio Caesarea.Metode: Metode penelitian menggunakan pendekatan case control. Populasi penelitian seluruh ibu bersalin di RSUD Dr. H. Moch. Ansari Saleh Banjarmasin tahun 2015 sebanyak 4776. Jumlah sampel case 515 sampel dengan teknik sampling total sampling dan sampel control 515 sampel dengan teknik sampel systematic random sampling. Pengumpulan data dengan teknik dokumentasi buku register persalinan. Analisis data dilakukan dengan uji Chi Square dengan (α=0,05).Hasil: Berdasarkan hasil penelitian didapatkan ada hubungan riwayat sectio caesarea sebelumnya (p=0,000) dengan (OR=19,529), letak sungsang (p=0,000) dengan (OR=2,717), makrosomia (p=0,000) dengan (OR=24,028), dan tidak ada hubungan preeklampsia berat (p=0,260) dengan persalinan sectio caesarea.Simpulan: Indikasi Relatif yang berhubungan dengan sectio caesarea adalah riwayat sectio caesarea, Letak sungsang dan makrosomia. Sedangkan preeklampsia berat tidak berhubungan dengan persalinan sectio caesarea.Kata Kunci:      Indikasi Relatif, Sectio Caesarea